Improvement of the thermal performance of louvered fin heat exchangers - Ribeiro Proenca Brojo, F. M. (Cranfield University, 2003)
Louvered-fin heat exchangers are used in the refrigeration systems of internal combustion engines (radiators) to dissipate the waste energy produced. Nevertheless, several authors state that this type of geometry can be applied with success to HVAC systems, since they are lightweight, compact, and capable of high heat fluxes without disproportional increase of the flow resistance. In this study, it is intended to extend the range of flow velocities and fluid temperatures generally studied in order to achieve results that could be applied in the design of louvered-fin heat exchangers applicable to HVAC systems. Louver-fin heat exchangers can exhibit several geometrical configurations. They can have round or flat tubes, splitter plates, triangular channels, rectangular channels, etc... Some of them can be considered as approximately two-dimensional as the louver plate fin and the corrugated louver-fin with rectangular channels (with or without splitter plate). The present study was directed towards the two-dimensional situation and heat transfer and pressure drop were quantified. In the first step performed, the parameters with possible influence were identified and ranges of use were chosen. Influence of the mesh size on the values of numerical results was quantified using the Richardson extrapolation methodology and the viability of its application to extrapolation in the case of unstructured grids was verified. Results of the mesh size study were applied to all subsequent numerical models in order to have grid independent results. A Parametric study using the Plackett-Burman design to identify the parameters of influence in the heat transfer and pressure drop was performed and correlations were determined having for base a Box- Behnken design. Finally a comparison with experimental results to validate numerical models was conducted. An attempt to construct a three-dimensional model was made and the results were presented and discussed.